2020
DOI: 10.1080/21870764.2020.1783749
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and formation mechanism of Gd2O2S:Pr3+,Ce3+ phosphors by sealed triple-crucible method

Abstract: Ln(NO 3) 3 • 6H 2 O (Ln = Gd, Pr and Ce), urea, sodium sulfite (Na 2 SO 3) and carbon powder were used as the starting materials. The precursor was synthesized with Ln(NO 3) 3 • 6H 2 O (Ln = Gd, Pr and Ce) solutions and urea at 95 °C for 4 h, and then the Gd 2 O 2 S:Pr 3+ ,Ce 3+ phosphors were prepared by calcined the precursor (in inner crucible), Na 2 SO 3 (in middle crucible) and carbon powder (in outer crucible) at 1000 °C for 2 h in a sealed environment. The X-ray powder diffraction (XRD) results confirm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…[ 21 ] also reported that the introduction of an appropriate amount of flux H 3 BO 3 was helpful to the enhancement of the fluorescence intensities of CaAl2O 4 : Eu 2+ , and Nd 3+ ; moreover, Sang et al. [ 22 ] showed a high‐temperature solid‐phase method using Ln(NO 3 ) 3 ‐6H 2 O (Ln = Gd, Pr, Ce), urea, sodium sulfite (Na 2 SO 4 ) and carbon powder as raw materials, and improved the traditional high‐temperature solid‐phase method by introducing the precipitation method to prepare the precursor, and then synthesized Gd 2 O 2 S: Pr 3+ , Ce 3+ phosphors by the sealed three‐crucible method, which not only prevented the carbon contamination but also improved the luminescence performance of the phosphors.…”
Section: Preparation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 21 ] also reported that the introduction of an appropriate amount of flux H 3 BO 3 was helpful to the enhancement of the fluorescence intensities of CaAl2O 4 : Eu 2+ , and Nd 3+ ; moreover, Sang et al. [ 22 ] showed a high‐temperature solid‐phase method using Ln(NO 3 ) 3 ‐6H 2 O (Ln = Gd, Pr, Ce), urea, sodium sulfite (Na 2 SO 4 ) and carbon powder as raw materials, and improved the traditional high‐temperature solid‐phase method by introducing the precipitation method to prepare the precursor, and then synthesized Gd 2 O 2 S: Pr 3+ , Ce 3+ phosphors by the sealed three‐crucible method, which not only prevented the carbon contamination but also improved the luminescence performance of the phosphors.…”
Section: Preparation Methodsmentioning
confidence: 99%
“…[19] For the high-temperature solid-phase method, temperature, pressure, charge compensator, and flux are important indicators that affect the luminescence properties of the materials. For example, Yang et al [20] found that the luminescence intensity of Sr 2 CeO 4 : Eu 3+ was enhanced with the increase of calcination temperature in the range of 900-1100 °C; Teng et al [21] also reported that the introduction of an appropriate amount of flux H 3 BO 3 was helpful to the enhancement of the fluorescence intensities of CaAl2O 4 : Eu 2+ , and Nd 3+ ; moreover, Sang et al [22] showed a high-temperature solid-phase method using Ln(NO 3 ) 3 -6H 2 O (Ln = Gd, Pr, Ce), urea, sodium sulfite (Na 2 SO 4 ) and carbon powder as raw materials, and improved the traditional hightemperature solid-phase method by introducing the precipitation method to prepare the precursor, and then synthesized Gd 2 O 2 S: Pr 3+ , Ce 3+ phosphors by the sealed three-crucible method, which not only prevented the carbon contamination but also improved the luminescence performance of the phosphors.…”
Section: High-temperature Solid-state Synthesismentioning
confidence: 99%